ANALYSIS OF THE IMPLEMENTATION OF THE ACADEMIC SUPERVISION MODEL IN ENHANCING THE PROFESSIONALISM OF PRIMARY SCHOOL TEACHERS - Barid Sholihah; Sri Marmoah; Roemintoyo (SOSIOEDUKASI, 2026)
This study was motivated by the fact that the implementation of academic supervision in primary schools still faces various obstacles, meaning that the enhancement of teachers’ professionalism has not yet been optimally achieved. The objectives of this study are (1) to analyse the application of the academic supervision model in enhancing teachers’ professionalism at SDN 01 Delingan, (2) to identify the obstacles to the implementation of academic supervision, and (3) to propose solutions for its implementation. The study employed a qualitative case study approach. The research subjects were the headteacher and primary school teachers. Data were collected through observation, in-depth interviews, and document analysis. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The research findings are: (1) academic supervision has been implemented through planning, execution, and follow-up, but remains oriented towards administrative and evaluative aspects; (2) the main constraints are time constraints, the school principal’s workload, and teachers’ perceptions of supervision; and (3) the solutions implemented include scheduling supervision and strengthening communication. The research findings provide practical significance for the development of more collaborative academic supervision, as well as a theoretical contribution to the study of academic supervision in enhancing teacher professionalism